Numerical analysis of stress singularities at the tip of intersecting 3d wedge-shaped cracks - Korepanova, Tatiana Olegovna; Matveenko, Valery Pavlovich; Sevodina, Natalia Vitalievna (Computational Continuum Mechanics, 2011)
We consider a variant of the method of constructing singular solutions for three-dimensional intersecting cracks. The results of calculation of stress singularity indices at the tip of a wedge-shaped crack obtained at different boundary conditions on the crack faces and at the common tip of intersecting wedge-shaped cracks are presented.
Keywords: stress singularity; wedge-shaped cracks; finite-element method